MORAL VALUES IN THE "HARRY POTTER AND THE DEATHLY HALLOWS” BY J.K ROWLING - Rani Dwi Sukmayanti; Muljani A. Nurhadi (INFERENCE: Journal of English Language Teaching, 2019)
Abstract. The purpose of the research is to find out the character and moral value in “The Harry Potter and The Deathly Hallows” by J.K Rowling. This research is designed as qualitative research. The approach that the writer uses is qualitative approach. The method that is used by the writer is content analysis method. The data are collected by analyzing the data found in the movie. The analysis of the movie is undertaken on the dialogues. The results of the research are the kinds of character and the moral value. 1) The kinds of character according to Russel in “The Harry Potter and The Deathly Hallows” is 53% for Protagonist character, 29% for Antagonist character and 18% for Foil character. The highest number is in protagonist and antagonist character because both of characters has a strong role in the movie. 2) The kinds of moral value according to Borba in “The Harry Potter and The Deathly Hallows” is 29% for Respect, 21% for Kindness, 16% for Empathy, 13% for Self-control, 11% for Fairness, 5% for Conscience and 5% for Tolerance. Respect aspect gets the highest number because the character who shows the respect in the movie is not only the protagonist but also the foil character.Keywords: : character; moral; value; moral value; film.